RPS12 increases the invasiveness in cervical cancer activated by c-Myc and inhibited by the dietary flavonoids luteolin and quercetin. (December 2015) - Lin, Cheng-Wei; Lai, Gi-Ming; Chen, Ku-Chung; Lin, Tsung-Han; Fan, Jhen-Jia; Hsu, Rhu-Long; Chou, Chih-Ming; Lin, Chun-Mao; Kandaswami, Chithan C.; Lee, Ming-Ting; Cheng, Chia-Hsiung
Highlights: The luteolin and quercetin, inhibited c-Myc activation was performed through Akt/mTOR signalling. The inhibition of c-Myc repressed RPS12 function in cell mobility of cervical cancer. The highly c-Myc and RPS12 expression increased cell mobility in A431-III cells. The RPS12 could be a potential therapy target for inhibition of cancer metastasis. Abstract: The dietary flavonoids luteolin and quercetin are reported to inhibit cancer mobility; however, the regulatory effect of luteolin and quercetin on RPS12 is still unclear. Here, we found that A431-III cells expressed a higher level of RPS12 than A431-P cells. The flavonoids luteolin and quercetin reduced RPS12 and c-Myc expressions via Akt/mTOR signalling. The Akt inhibitor LY294002 and mTOR inhibitor rapamycin reduced RPS12 and c-Myc expressions. The c-Myc inhibitor 10058-F4 reduced RPS12 expression and promoter transactivation. The overexpression of c-Myc increased RPS12 expression. Akt, mTOR, and c-Myc inhibitor blocked cell migration. Reducing RPS12 expression via 10058-F4 and shRNAs reduced cell invasion. This study reveals that RPS12 is upregulated via Akt/mTOR/c-Myc signalling and increased cell mobility. Luteolin and quercetin blocked Akt/mTOR/c-Myc signalling to reduce RPS12 level and downstream cell mobility. These data suggest a possible role of RPS12 in cell mobility and may be a potential therapy target for cervical cancer.